Assessment of the therapeutic efficacy of various drugs against cryptosporidiosis in calves - E. S. Klimova; M. E. Mkrtchyan; I. S. Ivanov; T. G. Krylovay (Российский паразитологический журнал, 2021)
The purpose of the research is studying the spread of cryptosporidiosis in calves and assessment of the extenseeffectiveness of antiprotozoal drugs.Materials and methods. The spread, seasonal and age-specific trends of cryptosporidiosis was studied on 395 spontaneously infected animals of five age groups. The first group was formed of calves up to 10 days of age, the second group of calves aged from 11 days to 2 months, the third group of calves from 2 to 4 months, the fourth group of calves from 4 to 6 months of age, and the fifth group of young animals from 6 months up to 1 year. To assess the efficacy of various drugs against cryptosporidiosis in calves, 5 groups of infected animals (4 experimental and 1 control), 10 animals each, were formed according to the principle of analogous pairs. The infection rate in cattle was determined by generally accepted coprological flotation methods, as well as by native smears with further staining according to Ziehl-Nielsen. We also considered clinical signs of cryptosporidiosis (diarrhea, dehydration).Results and discussion. We established the widespread occurrence of cryptosporidiosis in cattle on the farms of the Igrinsky, Uvinsky, Zavyalovsky Districts of the Udmurt Republic. The infection rate ranged from 20.25 to 80.0%. The largest percentage of infected calves was observed in the winter-spring period which was associated with the synchronization of the reproductive cycles of cows and a decrease in the resistance of the animal organism. Toltarox 5% and Galokur drugs in work environments showed 100% extense-effectiveness. It is not recommended to apply Amprolium 25% on these farms due to the low efficacy and the development of parasite resistance to this drug.